Revisiting the Arthashastra : An Approach to Emotional Intelligence - Mohanty, Amrita; Das, Ganesh Prasad (Prabandhan: Indian Journal of Management, 2017)
The concept of emotional intelligence is a well known behavioral construct among students, teachers, and researchers in the area of organizational behavior and psychology throughout the world. Still, it is imperative to redefine the different aspects of emotional intelligence in the context of the prevailing aggressive global atmosphere. The achievement and failure of a company chiefly depends upon the productive and effective handling of resources available within the organization. Resources are categorized into two like : human and non-human. Successful and productive uses of non -human resources are possible only through highly motivated and committed human beings.Â Motivation and commitment among the work force are shaped and injected through the dynamic leadership of managers. One of the vital aspects of effective leadership is to develop the ability to perceive emotions within one self and others. Leadership also involves expressing emotions effectively. The whole process of perceiving and expressing emotions effectively pose a greater challenge before today’s managers to motivate and mobilize their subordinates. In order to bridge the expected gap existing in the present emotional intelligence aspects, a paradigm shift came into view by means of instilling contemporary management thoughts through the nuances of age-old insights. The article examined the book Arthashastra authored by Kautilya, the chief exponent in the field of economics and management. Arthashastra etymologically explains â€œthe science of wealthâ€ and is one of the ancient Indian works that emphasizes upon the effective management of wealth through leadership. Arthashastra illustrates the contribution of Kautilya in ancient India regarding the role of an emotionally intelligent king towards the effective administration of the state. The paper explored the lessons in emotional intelligence from Arthashastra and interpreted its relevance in the present day business context. The relevance of Arthashastra in the perspective of emotional intelligence was analyzed in this paper.